EFFECT OF GLOBAL MINDSET AND ENTREPRENEURIAL MOTIVATION TO ENTREPRENEURIAL SELF-EFFICACY AND IMPLICATION TO ENTREPRENEURIAL INTENTION - Aima, M. Havidz; Suta Achmad Wijaya; Lenny Carawangsa; Ma Ying (Dinasti International Journal of Digital Business Management, 2020)
The research method used a quantitative approach, which the sample of in this study were 100 Stdents of Faculty of Economics of Mercu Buana University (MBU), Jakarta, academic year 2019/2019 as the representative of the population of Faculty of Economics at the same year. Data collection techniques using interview and questionnaire. The questionnaire survey instrument was delivered to the respondents. Data were analyzed by using structural equation model (SEM) with the Smart PLS3.0 software program. This study reveals that the global mindset significantly influence to entrepreneur self-efficacy and to Entrepreneur Intention. Otherwise, entrepreneur moti-vation has no significant effect to entrepreneur self-efficacy and to entrepreneur intention. Self-Efficacy significantly mediate Globbal Mindset to Entreprepr-eneurial Intention, but it does not significantly mediate Entrepreneurial Motivation to Entrepreneurial Intention. Other finding, Global Mindset and Entrepreneurial Motivation are simultaneously and significantly influence Self-Efficacy; and three of proposed variable are simultaneuosly and significantly influence Entrepreneurial Intention. Refers to the research finding, the main factor to anyone to become as an Entrepreneur is mindset. Thus, one should have been involve with Entrepreneurship activity trough first hand experience from a young age